Identification of N-(5-(phenoxymethyl)-1, 3, 4-thiadiazol-2-yl)acetamide derivatives as novel protein tyrosine phosphatase epsilon inhibitors exhibiting anti-osteoclastic activity. Issue 18 (1st October 2018) - Ku, Bonsu; Yun, Hye-Yeoung; Lee, Kyung Won; Shin, Ho-Chul; Lee, Sang-Rae; Kim, Chang Hyen; Park, Hwangseo; Yi, Kyu Yang; Lee, Chang Hoon; Kim, Seung Jun
Graphical abstract: Abstract: Cytosolic protein tyrosine phosphatase epsilon (cyt-PTPε) plays a central role in controlling differentiation and function of osteoclasts, whose overactivation causes osteoporosis. Based on our previous study reporting a number of cyt-PTPε inhibitory chemical compounds, we carried out a further and extended analysis of our compounds to examine their effects on cyt-PTPε-mediated dephosphorylation and on osteoclast organization and differentiation. Among five compounds showing target selectivity to cyt-PTPε over three other phosphatases in vitro, two compounds exhibited an inhibitory effect against the dephosphorylation of cellular Src protein, the cyt-PTPε substrate. Moreover, these two compounds caused destabilization of the podosome structure that is necessary for the bone-resorbing activity of osteoclasts, and also attenuated cellular differentiation of monocytes into osteoclasts, without affecting cell viability. Therefore, these findings not only verified anti-osteoclastic effects of our cyt-PTPε inhibitory compounds, but also showed that cyt-PTPε expressed in osteoclasts could be a putative therapeutic target worth considering.